Role of intraoperative wound irrigation with antibiotics in reducing surgical site infection in patients undergoing contaminated and dirty midline laparotomy surgical wound: a pilot study - P., Sandhiya; S., Sureshkumar; C., Vijayakumar; C., Palanivel (International Surgery Journal, 2018)
Background: This study was carried to assess the effect of antibiotic wound irrigation in reducing the surgical site infection (SSI) in the patients undergoing midline laparotomy with contaminated and dirty surgical incision wound. Methods: All patients operated with class-IV- dirty and class III (contaminated) abdominal operative wound according to CDC (Centre for Disease Control and Prevention) were included in this pilot study. Study patients were divided into antibiotic irrigation group and control group. In control group, after rectus sheath closure, the wound was irrigated with 100 mL of normal saline before the skin closure. In antibiotic irrigation group, after rectus sheath closure, the wound was irrigated with Ceftriaxone (10 mL) and Metronidazole (100 mL). Incidence of SSI, degree of SSI and length of hospitalization were compared between two groups. Results: A total of 40 patients were included in the study, 20 in each group. Both the groups were comparable with respect the age, gender, co-morbidities and class of surgical wound. The incidence of SSI was lesser [10% versus 35%; p=0.06] in the antibiotic irrigation group compared to control group. However, the difference was not statistically significant. The length of hospitalization between the groups were comparable [13.5 versus 14.7 days; p=0.74]. The pain score was also not significantly different between the two groups. Conclusions: On comparing to saline irrigation, antibiotic irrigation in patients with contaminated and dirty operative wound results in a lesser SSI with comparable hospital stay and postoperative pain. However, the difference was not statistically significant.